Plasma Cytokine Levels in Fibromyalgia and Their Response to 15 Weeks of Progressive Resistance Exercise or Relaxation Therapy - M. Ernberg; N. Christidis; B. Ghafouri; I. Bileviciute-Ljungar; M. Löfgren; J. Bjersing; A. Palstam; A. Larsson; K. Mannerkorpi; B. Gerdle; E. Kosek (Mediators of Inflammation)
The aims of this study were to compare circulating cytokines between FM and healthy controls and to investigate the effect on cytokine levels by 15 weeks of progressive resistance exercise or relaxation therapy in FM. Baseline plasma cytokine levels and clinical data were analyzed in 125 women with FM and 130 age-matched healthy women. The FM women were then randomized to progressive resistance exercise (n=49) or relaxation (n=43). Baseline IL-2, IL-6, TNF-α, IP-10, and eotaxin were higher in FM than in healthy controls (P<0.041), whereas IL-1β was lower (P<0.001). There were weak correlations between cytokine levels and clinical variables. After both interventions, IL-1ra had increased (P=0.004), while IL-1β had increased in the relaxation group (P=0.002). Changes of IFN-γ, IL-2, IL-4, IL-6, IL-8, and IL-17A were weakly correlated with changes of PPT, but there were no significant correlations between changes of cytokine and changes in other clinical variables. The elevated plasma levels of several cytokines supports the hypothesis that chronic systemic inflammation may underlie the pathophysiology of FM even if the relation to clinical variables was weak. However, 15 weeks of resistance exercise, as performed in this study, did not show any anti-inflammatory effect on neither FM symptoms nor clinical and functional variables. This trial is registered with ClinicalTrials.govNCT01226784, registered October 21, 2010. The first patient was recruited October 28, 2010.